The Maritime Analysis and Operations Center (Narcotics) in Lisbon – a background paper on the foundation and successes of the EU's prime law enforcement body for the prevention of Transatlantic narcotic drug smuggling - Carsten Weerth (Customs Scientific Journal, 2022)
Narcotic drugs are smuggled from the Americas to Europe and many parts of the World. While opium, cannabis, hashish or other drugs are mainly coming out of Asia or Africa and are channelled and smuggled to Europe mostly on a land passage (or very short maritime routes), cocaine is mostly produced in Columbia, Peru and Bolivia but also other South and middle American countries and is trafficked to North America and Europe and other parts of this globe by help of smuggling on airplanes and maritime smuggling pathways. The European War on Drugs concerning cocaine and the transatlantic smuggling pathway is depending on the interception of this maritime smuggling pathway since large quantities are shipped on the sea way and only smaller quantities are trafficked by aircrafts. The smuggling techniques are varying as are the common and joint law enforcement strategies. This background paper describes the Maritime Analysis and Operations Center (Narcotics) of the European Union that has been founded by seven EU member states in 2007 and which is an EU law enforcement unit that aims at intercepting the drug smuggling in the Atlantic Ocean. It is run by the Portuguese Government in Lisbon, co-financed by the EU and is co-operating with law enforcement units in the USA, South America and Africa as well as INTERPOL and EUROPOL. The paper starts with the original wording of the MAOC (N) self-description and its mission statement. It focusses on the international cooperation of the MAOC (N): Success stories and seizures of the last two years 2020/2021 are listed and shortcomings and possible future co-operations are discussed. Furthermore it discusses limitations and omissions of the MAOC (N). Finally it concludes that more EU member states should contribute actively in the management and operations of the MAOC (N).
Keywords: F53; K33; K42; 330; International Customs Law; Illicit Trade; Law enforcement; War on Drugs